Barking Dogs Never Bite - Bong Joon-ho; Cho Yong-kyou; Jo Yeong-gyu; Lee Sung-jae; Bae Du-Na; Byeon Hie-bong (MFA, 2011)
Yun-ju (Lee Sung-jae) leads a cheerless life. His domineering, pregnant wife (Kim Ho-jeong) has him cracking walnuts on a whim and his teaching career looks bound for nowhere if he doesn't raise $10,000 fast as a bribe for his professorship. Save the pity party for someone else though because Yun-ju's way of dealing with the chip on his shoulder is to kill the yapping lapdogs in his apartment building. Once you've seen him off a beribboned terrier and a toy doberman, you're kind of glad that he's got it so bad. And anyway, someone else is in greater need of your sympathy. That's Hyeon-nam (Bae Dun-na), the management company's spacey bookkeeper who's on a mission to find the dog-killer and a purpose in life. Because this is a Bong Joon-ho film, the narrative ends up being much more than those two intertwining tales. There are also subplots involving an indiscriminate janitor who tells good ghost stories, a crazy old lady who dries radishes on the roof, and a homeless man whose bad luck ends up seeming to work in his favor. [koreangrindhouse.blogspot.de]